2016
DOI: 10.1074/jbc.m115.699504
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transmembrane Bile Acid Receptor TGR5 Modulates Pancreatic Islet α Cells to Promote Glucose Homeostasis

Abstract: The physiological role of the TGR5 receptor in the pancreas is not fully understood. We previously showed that activation of TGR5 in pancreatic ␤ cells by bile acids induces insulin secretion. Glucagon released from pancreatic ␣ cells and glucagonlike peptide 1 (GLP-1) released from intestinal L cells regulate insulin secretion. Both glucagon and GLP-1 are derived from alternate splicing of a common precursor, proglucagon by PC2 and PC1, respectively. We investigated whether TGR5 activation in pancreatic ␣ cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 52 publications
0
95
1
1
Order By: Relevance
“…Activation of TGR5 has been shown to protect against inflammation in the intestine and liver [50], stimulate GLP-1 secretion from enteroendocrine L cells and insulin synthesis and secretion from pancreatic β-cells [41, 75], and protect cholangiocytes from bile acid toxicity in cholestasis. Thus, it is a potential therapy for cholestasis [50].…”
Section: Bile Acids As Therapeutic Agentsmentioning
confidence: 99%
“…Activation of TGR5 has been shown to protect against inflammation in the intestine and liver [50], stimulate GLP-1 secretion from enteroendocrine L cells and insulin synthesis and secretion from pancreatic β-cells [41, 75], and protect cholangiocytes from bile acid toxicity in cholestasis. Thus, it is a potential therapy for cholestasis [50].…”
Section: Bile Acids As Therapeutic Agentsmentioning
confidence: 99%
“…As a result, TGR5 could be activated by WB403 to improve glucose tolerance, decrease fasting blood glucose and the glycosylated hemoglobin A1c (HbA1c) in T2D mice (Zheng et al, 2015). In the new reports, Kumar et al (2016) shown that TGR5 induced GLP-1 release from pancreatic α cells via an Epac-mediated PKA-independent mechanism. Agarwal et al (2016) also shown the important roles of TGR5 in T2D.…”
Section: Tgr5 and Different Diseasesmentioning
confidence: 99%
“…Li et al, 2011), modulates energy expenditure (Watanabe et al, 2006), stimulates GLP-1 release from intestinal L cells (Habib et al, 2013; Katsuma et al, 2005; Thomas et al, 2009), suppresses hepatic glycogenolysis (Potthoff et al, 2013) reduces inflammation (Frikke Schmidt et al, 2016) and inflammatory macrophage activation (Kawamata et al, 2003; Keitel et al, 2008; Lou et al, 2014; Maruyama et al, 2002; Y. D. Wang et al, 2008), improves pancreatic function (Kumar et al, 2016; Vettorazzi et al, 2016) and improves non-alcoholic fatty liver disease (Ding et al, 2016). TGR5 knockout mice have mildly reduced BA pools (Maruyama et al, 2006; Vassileva et al, 2006), impaired glucose tolerance (Thomas et al, 2009) and exacerbated inflammatory responses (Péan et al, 2013).…”
Section: Bile Acidsmentioning
confidence: 99%